Design of Dual-Band Filters with Individually Controllable Passband Responses and Orders - Tan, Eng Leong (2017)
This paper presents a novel design of dual-band filters with individually controllable passband responses and orders. Besides the center frequency and bandwidth, the response and order of each passband can be different and controlled individually. The dual-band filter is formed by synthesizing each filter element (resonator, inverter) one by one, exploiting the corresponding individual single-band filters design tables/formulas for different prototype responses and orders. Trisection stepped-impedance resonators (TSSIR) are adopted with novel considerations as dual-band resonators, whose additional design parameters could help to realize the required in-band responses (resonances, slope parameters) and improve simultaneously the out-of-band performances (transmission zeros of TSSIR). Furthermore, they can be used to design a dual-band filter with far separation between two passbands. Meanwhile, stepped-impedance inverters are chosen as dual-band inverters with novel additional conditions to obtain symmetric passbands, which can also provide different inverter immittance parameters J/K at two center frequencies when the response or order of each passband is different. To illustrate the two passbands being controlled individually, two dual-band filters with different orders and responses are demonstrated.